Textile and laundry in hotel industry / D K Aggarwal - Aggarwal, D. K.
Hotel Laundry Operations Essential Tips for Laundry Management Responsibilities of Laundry Manager Cleaning and Stain Removal Table Cloths and Napkins Use of Carpets and Pads Carpet Installation Carpet Maintenance Uses and Cleaning of Rugs Selection and Maintenance of Curtains Maintenance of Bedding.